Identification in Drosophila melanogaster of the invertebrate G protein-coupled FMRFamide receptor - Meeusen, Tom (National Academy of Sciences, 2002)
We here describe the cloning and characterization of the functionally active Drosophila melanogaster (Drm) FMRFamide receptor, which we designated as DrmFMRFa-R. The full-length ORF of a D. melanogaster orphan receptor, CG 2114 (Berkeley Drosophila Genome Project), was cloned from genomic DNA. This receptor is distantly related to mammalian thyroid-stimulating hormone-releasing hormone receptors and to a set of Caenorhabditis elegans orphan receptors. An extract of 5,000 central nervous systems from the related but bigger flesh fly, Neobellieria bullata (Neb), was used to screen cells expressing the orphan receptor. Successive purification steps, followed by MS, revealed the sequence of two previously uncharacterized endogenous peptides, APPQPSDNFIRFamide (Neb-FIRFamide) and pQPSQDFMRFamide (Neb-FMRFamide). These are reminiscent of other insect FMRFamide peptides, having neurohormonal as well as neurotransmitter functions. Nanomolar concentrations of the Drm FMRFamides (DPKQDFMRFamide, TPAEDFMRFamide, SDNFMRFamide, SPKQDFMRFamide, and PDNFMRFamide) activated the cognate receptor in a dose-dependent manner. To our knowledge, the cloned DrmFMRFa-R is the first functionally active FMRFamide G protein-coupled receptor described in invertebrates to date.